Gender, academic careers and the sabbatical: a New Zealand case study. Issue 3 (3rd May 2016) - Smith, D.; Spronken-Smith, R.; Stringer, R.; Wilson, C. A.
ABSTRACT: This article examines academics' access to and perceptions of sabbaticals at a research-intensive university in New Zealand. Statistical and inductive analysis of survey data from 915 academics (47% of all academics employed) revealed inequalities in access to and experience of sabbaticals, and highlighted academic, personal and gender issues. Men and women were generally united in their views on how family circumstances, children, childcare, partners, unfairness, inequity, transparency and finances, affected ability to take sabbatical leave, and that lack of transparency and gatekeeping were barriers to access. Yet, women indicated greater concern than men about the application process, adequacy of leave and the role of the Head of Department in accessing sabbaticals. Women were also significantly more likely to be ineligible for sabbaticals owing to casual employment status, and women who were eligible tended to take fewer, shorter sabbaticals. Academics view sabbaticals as vital for career progression and the findings highlight the need to facilitate equitable access to sabbatical leave across an institution. Universities need to audit the uptake of sabbaticals by eligible academics and review the processes associated with application, approval and support for sabbatical leave.